PENGARUH PENGGUNAAN METODE STEAM TERHADAP PERKEMBANGAN KOGNITIF ANAK USIA 4-5 TAHUN DI KOBER AL HIDAYAH - Susanti, Susi; Hidayat, Yusuf; Sarip, Sri Kurnia (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
This study investigated the effectiveness of the Science, Technology, Engineering, Art, and Mathematics (STEAM) method in enhancing the early childhood’s cognitive development of 4-5 years old at Kober Al Hidayah. The STEAM method emphasizes the interconnectedness of knowledge and skills. This study employed a quantitative method under pre-experimental design. The findings of the study found that before being given the implementation of the STEAM method, the early childhood’s cognitive development of 4-5 years old at Kober Al Hidayah showed "Quite Good”. Meanwhile, after being given the implementation of the STEAM method, the early childhood’s cognitive development of 4-5 years old at Kober Al Hidayah showed "Very Good". Furthermore, the t-test supported the findings which shiwed t-observed > t-table at which the score 9.347 > 2.145 alt al significalnce level of 5%. These findings led to the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. Thus, statistically there was positive effect on the implementation of the STEAM method on the early childhood’s cognitive development of 4-5 years old at Kober Al Hidayah. Keywords:  ealrly childhood; cognitive; the STEALM method